PENGARUH KEMAMPUAN EKONOMI ORANG TUA TERHADAP HASIL BELAJAR MATEMATIKA DI SEKOLAH DASAR - Muhdar, Rahmat (Program Studi Pendidikan Ekonomi Institut Sain dan Kependidikan (ISDIK) Kie Raha Maluku Utara, 2024)
In remote areas in Indonesia, there are still gaps in the education that Indonesian children should receive. There are various factors that cause this gap. The aim of writing the article is to analyze critically and in depth the influence of parents' socio-economic status on student learning outcomes in elementary schools. This type of article is written using qualitative research using analytical literature studies and also research related to books, articles, journals, or other relevant sources that are continuous with the title. The conclusion is that good parental socio-economic conditions can improve student learning achievement so that the learning outcomes obtained by students will also be as good as possible. This is because the family has sufficient facilities and infrastructure so that it can support the talents and interests of students. However, in this research it does not rule out the possibility for a person or child not to make efforts to obtain good achievement and learning outcomes for a child who comes from a family with a sufficient socio-economic status. Many of the children come from remote areas to continue to participate in the teaching and learning process as well as possible. This is because they are aware of the importance of their education.